Essential oil of leaves of Cinnamomum tamala Nees. & Eberm. from North East India - SINGH, S C NATH, A K HAZARIKA, R S (Journal of Spices and Aromatic Crops, 1994)
An essential oil (0.7%) having nD 28 = 1.4791 obtained by hyclrodistillation of fresh leaves of Cinnamomum tamala cultivated in North Cacher Hills of North East India was examined by gas chromatography. Fourteen oil components were identified which constituted 93.44% of the oil. Linalool was the main component (60.73%), whereas eugenol and cinnamic aldehyde were detected in trace amounts (<1%). Other components of significant occurrence (3%) in the oil were a-pinene (10.54%), b-pinene (10.42%), limonene (3.21%) and camphene (3.06%).